Pengenalan Eksperimen Sederhana dalam Pembelajaran untuk Meningkatkan Minat Belajar Siswa Madrasah Aliyah Negeri 2 Kabupaten Lombok Tengah - Lalu Ahmad Didik Meiliyadi; Rima Buana Prahastiwi; Kurniawan Arizona; Muhammad Zainur Rahman (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
Community service has been carried out in the form of introducing simple experiments in learning which is expected to increase students' interest in learning physics. The method used in this introduction activity is direct experimentation. The experiments given are related to pressure and optics. In general, the service activities are carried out in 4 stages, namely preparation, socialisation, implementation and evaluation and reflection. The service activities have been carried out well. Based on the activity evaluation questionnaire, it shows that most students are satisfied and enthusiastic in carrying out experiments. However, the highlight is the time aspect. This is because students feel that the time given in discussing each material is not enough. In general, based on the questionnaire students feel motivated in learning through experiments followed by theoretical learning.